Focal Epilepsy in Children With Tuberous Sclerosis Complex: Does Vigabatrin Control Focal Seizures?. (April 2022) - Lin, Sufang; Liao, Jianxiang; Zhao, Xia; Hu, Yan; Chen, Li; Chen, Yan; Liu, Guosheng; Yao, Yi; Su, Qiru; Scheffer, Ingrid E.; Wen, Feiqiu
We evaluated the efficacy and safety of vigabatrin in focal epilepsy associated with tuberous sclerosis complex by retrospectively reviewing patients with focal epilepsy and tuberous sclerosis complex treated with vigabatrin at a pediatric epilepsy center over an 8-year period. Of 85 patients, 20 (23.5%) were seizure-free for >12 months, 45 (52.9%) were responders (≥50% seizure reduction), and 20 (23.5%) were nonresponders. The median age (in months) at seizure onset in the seizure-free group (median, 15; interquartile range [IQR], 6-23.3) was higher than that of responders (median, 5; IQR, 3-14) and nonresponders (median, 6; IQR, 2-12). Fewer patients in the seizure-free group had calcification in their largest tubers, but the presence of tuber calcification did not differ among groups. Vigabatrin is more likely to result in seizure freedom in children with tuberous sclerosis complex who have later infantile onset of focal seizures and no calcification in their largest tuber.